Enculturated Education for Strengthening Character Education in Preventing Intolerance and Radicalism - Cardinale, Pamela; Rofi’i, Muhammad Syaroni; Samputra, Palupi Lindiasari; Achdiawan, Ramadhani (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
AbstractIntolerance and extremism have recently increased in the academic atmosphere or among students. The purpose of this study was to discover the origins of intolerance and radicalism among students, identify the core cause of educational problems, and examine the role of cultural education in building the character of Indonesian students. The Delphi approach was used to assess data gathered from a variety of expert informants. The study's findings revealed four significant causes of intolerance and radicalization: personal factors, education, economic-social-political-cultural issues, and a lack of religious comprehension. The study also found that religious education is less in-depth, with less reading, weak persuasive logic, and a focus on binary truth. Cultural education begins with establishing superior national identity through the Pancasila character (